A review of the immune molecules in the sea cucumber. Issue 1 (May 2015) - Xue, Zhuang; Li, Hui; Wang, Xiuli; Li, Xia; Liu, Yang; Sun, Jing; Liu, Cenjie
Abstract It is very important to identify and characterize the immune-related genes that respond to pathogens. Until recently, only some of the immune-related genes in sea cucumbers had been characterized. Their expression patterns after pathogen challenges have been analyzed via expressed sequence tag libraries, microarray studies and proteomic approaches. These genes include lectins, antimicrobial peptides, lysozyme, enzymes, clotting protein, pattern recognition proteins, Toll receptors, complement C3 and other humoral factors that might participate in the innate immune system of sea cucumbers. Although the participation of some of these immune molecules in the sea cucumber's innate immune defense against invading pathogens has been demonstrated, the functions of many of the molecules remain unclear. This review focuses on the discovery and functional characterization of the immune-related molecules from the sea cucumber for the first time and provides new insights into the immune mechanisms of the sea cucumber, which opens new possibilities for developing drugs for novel anti-bacterial and antiviral applications in fisheries.